Anthropogenic Iron Deposition Alters the Ecosystem and Carbon Balance of the Indian Ocean Over a Centennial Timescale. Issue 2 (14th February 2021) - Pham, Anh L. D.; Ito, Takamitsu
Abstract: Phytoplankton growth in the Indian Ocean is generally limited by macronutrients (nitrogen: N and phosphorus: P) in the north and by micronutrient (iron: Fe) in the south. Increasing atmospheric deposition of N and dissolved Fe (dFe) into the ocean due to human activities can thus lead to significant responses from both the northern and southern Indian Ocean ecosystems. Previous modeling studies investigated the impacts of anthropogenic nutrient deposition on the ocean, but their results are uncertain due to incomplete representations of the Fe cycling. This study uses a state‐of‐the‐art ocean ecosystem and Fe cycling model to evaluate the transient responses of ocean productivity and carbon uptake in the Indian Ocean, focusing on the centennial time scale. The model includes three major dFe sources and represents an internal Fe cycling modulated by scavenging, desorption, and complexation with multiple, spatially varying ligand classes. Sensitivity simulations show that after a century of anthropogenic deposition, ecosystem responses in the Indian Ocean are not uniform due to a competition between the phytoplankton community. In particular, the competition between diatom, coccolithophore, and picoplankton alters the balance between the organic and carbonate pumps in the Indian Ocean, increasing the carbon uptake along 50°S and the southeastern tropics while decreasing it in the Arabian Sea. Our results reveal the important role of ecosystem dynamics in controlling the sensitivity of carbon fluxes in the Indian Ocean under the impact of anthropogenic nutrient deposition over a centennial timescale. Plain Language Summary: Human activities have intensified the atmospheric nutrient input into the Indian Ocean where the marine ecosystem is diverse and biogeochemical features are complex. Thus, the response of the marine ecosystem in this region to human perturbations can be significant. Results from previous studies on this topic are uncertain due to our limited understanding of the ocean micronutrient, iron. In this study, we address this issue through a suite of computer simulations with an improved iron cycling model. We found that after a century of anthropogenic deposition, the ocean carbon uptake is enhanced in the southeastern tropics of the Indian Ocean. However, the carbon uptake decreases in the Arabian Sea because the ecosystem shifts toward organisms that produce calcite, which changes the ocean chemistry and weakens its ability to absorb carbon dioxide. Key Points: Ecosystem dynamics controls the centennial response of the Indian Ocean carbon cycling to anthropogenic nutrients depositions The competition between phytoplankton community leads to opposite responses of the ocean carbon uptake in different regions Iron distribution biases in previous modeling studies can underestimate the response of the ocean ecosystem